The Precarization of Educational Labor: The Examination of Teachers’ Job Insecurity Perceptions - Ibrahim Colak, Yahya Altinkurt (Educational Process: International Journal)
Background/purpose – In this study, the precarization of educational labor was identified in terms of teachers’ job insecurity perceptions. The purpose of the study was to examine the job insecurity perceptions of teachers with permanent, fixed-term, or temporary contracts.